Development of Learning Media with Learning Branching Program for the Learning of Fine Arts in Art Culture Lessons in SMA Negeri - Rahmat Taufan; Ridwan (International Journal on Integrated Education, 2022)
The phenomenon of learning that exists in Indonesia is currently oriented to educational issues that can make students better. The imbalance in the pattern of student perceptions, differences in the level of understanding of students, and the media used are still conventional. Lack of social awareness and knowledge of students about everyday art forms and cultural heritage. Learning media with the learning branching program can help adjust the speed level of students' understanding and help students learn actively and independently. The learning media with the learning branching program is equipped with enrichment and remedial which create the interaction process between students and learning media. The research objective is to produce media with a valid, practical, and effective learning branching program.